Analisis Pengaruh Faktor Internal Perbankan Syariah Dan makro Ekonomi Terhadap Pembiayaan Berbasis Bagi Hasil - Muti Atul Hasanah; Mulia Amirullah; Eris Munandar (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
This study aims to analyze in depth the influence of Third Party Funds (DPK), Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), Financing Deposit Ratio (FDR), and Inflation Rate on Profit Sharing Financing at Islamic Commercial Banks in Indonesia . This study uses secondary data. This study uses a quantitative descriptive approach using the Vector Error Correction Model (VECM). The results of this research data processing indicate that the results of the Granger Causality Test, there is a causality relationship to the DPK, NPF, and CAR variables on Profit Sharing Financing, but in the FDR and Inflation variables there is no causality relationship to Profit Sharing Financing. The CAR variable instrument based on the analysis of the results of the Vector Error Correction Model (VECM) Estimation Test has a significant positive impact with a high coefficient on Profit Sharing Financing. The CAR variable instrument based on the analysis of the results of the Impulse Response Function Test (IRF) is the variable that has the most and the highest shocks are responded to by the research variables. The CAR variable instrument based on the analysis of the Variance Decomposition (VD) test results is a variable that has a composition and a large role of shocks responded to by the research variables. The variable inflation instrument based on the analysis of the results of the Impulse Response Function (IRF) Test and the analysis of the Variance Decomposition (VD) Test has not occupied the largest response and the largest composition for other variables